Edge Radial Electric Field Formation after the L‐H Transition on JT‐60U. Issue 4 (June 2014) - Kamiya, K.; Matsunaga, G.; Honda, M.; Miyato, N.; Urano, H.; Kamada, Y.; Ida, K.; Itoh, K.; the JT‐60 team
Abstract Spatio‐temporal measurements of the impurity ion temperature, density, and rotation profiles around the plasma edge region have been made in the JT‐60U tokamak, allowing the determination of radial electric field, Er, with the key dimensionless parameter (poloidal Mach number, Upm) at the L‐H transition in a number of operational regimes. We found that there is variation in the L‐H transition in terms of its time‐scale; not only "hard" type transition with a faster time‐scale than that seen in the plasma transport (as represented by an energy confinement time, τE) as seen in the many conventional tokamaks, but also "soft" one with a slow time‐scale (≈τE) is possible solution, including a complex multi‐stage Er transition in the later H‐phase. The most important point is that the critical condition for the L‐H transition predicted by ion‐orbit loss model could be applicable only for "hard" transition (occurred at Upm ≥ 1), and not necessary for "slow" one (occurred even at Upm < 1). Characteristics of the turbulent density fluctuation with the frequency range of 100 kHz at the plasma edge region, in addition to a uniform toroidal MHD oscillation (i.e., n = 0), during ELM‐free H‐phase are also reported. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)